Implementation strategies for health systems in low-income countries: An overview of systematic reviews - Pantoja, Tomas (2017)
Background: A key function of health systems is implementing interventions to improve health, but coverage of essential health interventions remains low in low-income countries. Implementing interventions can be challenging, particularly if it entails complex changes in clinical routines; in collaborative patterns among different healthcare providers and disciplines; in the behaviour of providers, patients or other stakeholders; or in the organisation of care. Decision-makers may use a range of strategies to implement health interventions, and these choices should be based on evidence of the strategies' effectiveness. Objectives: To provide an overview of the available evidence from up-to-date systematic reviews about the effects of implementation strategies for health systems in low-income countries. Secondary objectives include identifying needs and priorities for future evaluations and systematic reviews on alternative implementation strategies and informing refinements of the framework for implementation strategies presented in the overview. Methods: We searched Health Systems Evidence in November 2010 and PDQ-Evidence up to December 2016 for systematic reviews. We did not apply any date, language or publication status limitations in the searches. We included well-conducted systematic reviews of studies that assessed the effects of implementation strategies on professional practice and patient outcomes and that were published after April 2005. We excluded reviews with limitations important enough to compromise the reliability of the review findings. Two overview authors independently screened reviews, extracted data and assessed the certainty of evidence using GRADE. We prepared SUPPORT Summaries for eligible reviews, including key messages, 'Summary of findings' tables (using GRADE to assess the certainty of the evidence) and assessments of the relevance of findings to low-income countries. Main results: We identified 7272 systematic reviews and included 39 of them in this overview. An additional four reviews provided supplementary information. Of the 39 reviews, 32 had only minor limitations and 7 had important methodological limitations. Most studies in the reviews were from high-income countries. There were no studies from low-income countries in eight reviews. Implementation strategies addressed in the reviews were grouped into four categories - strategies targeting: 1. healthcare organisations (e.g. strategies to change organisational culture; 1 review); 2. healthcare workers by type of intervention (e.g. printed educational materials; 14 reviews); 3. healthcare workers to address a specific problem (e.g. unnecessary antibiotic prescription; 9 reviews); 4. healthcare recipients (e.g. medication adherence; 15 reviews). Overall, we found the following interventions to have desirable effects on at least one outcome with moderate- or high-certainty evidence and no moderate- or high-certainty evidence of undesirable effects. 1.Strategies targeted at healthcare workers: educational meetings, nutrition training of health workers, educational outreach, practice facilitation, local opinion leaders, audit and feedback, and tailored interventions. 2.Strategies targeted at healthcare workers for specific types of problems: training healthcare workers to be more patient-centred in clinical consultations, use of birth kits, strategies such as clinician education and patient education to reduce antibiotic prescribing in ambulatory care settings, and in-service neonatal emergency care training. 3. Strategies targeted at healthcare recipients: mass media interventions to increase uptake of HIV testing; intensive self-management and adherence, intensive disease management programmes to improve health literacy; behavioural interventions and mobile phone text messages for adherence to antiretroviral therapy; a one time incentive to start or continue tuberculosis prophylaxis; default reminders for patients being treated for active tuberculosis; use of sectioned polythene bags for adherence to malaria medication; community-based health education, and reminders and recall strategies to increase vaccination uptake; interventions to increase uptake of cervical screening (invitations, education, counselling, access to health promotion nurse and intensive recruitment); health insurance information and application support. Authors' conclusions: Reliable systematic reviews have evaluated a wide range of strategies for implementing evidence-based interventions in low-income countries. Most of the available evidence is focused on strategies targeted at healthcare workers and healthcare recipients and relates to process-based outcomes. Evidence of the effects of strategies targeting healthcare organisations is scarce.